AUTHORIZATION OF HALAL CERTIFICATION IN INDONESIA, MALAYSIA AND SINGAPORE - Ridwan, Ahmad Hasan; Hasanuddin, Muhammad; Fatahillah, Ikhwan Aulia; Fauzia, Ine (International Journal of Psychosocial Rehabilitation, 2020)
The rapid development of the global halal industry has driven many countries to consider the halal industry. Southeast Asian countries including Indonesia, Malaysia, and Singapore are known as halal campaigners. These countries aspire to become a global halal hub. In order to realize this aspiration, they established an institution or agency to certify halal products. In Indonesia, it is managed by the Halal Certification Agency (BPJPH). Malaysia has the Department of Islamic Development (JAKIM) and Singapore has the Islamic Religious Council of Singapore (MUIS) or known as the Islamic Religious Council of Singapore. Halal certification in Malaysia and Singapore are voluntary, not mandatory as in Indonesia. Even though they do not have specific laws, in this case, these countries already have halal standardization. While Indonesia, currently still does not have an official standard issued by BPJPH and the halal standardization still uses LPPOM-MUI based on HAS 23000 MUI.